2012
DOI: 10.1016/j.dental.2012.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of resin monomers used in restorative dentistry

Abstract: Objectives The application of an electric field has been shown to positively influence the impregnation of the resin monomers currently used in dentin bonding systems during hybrid layer formation. This study presents an experimental characterization of the electrical properties of these monomers with the aim of both correlating them to their chemical structures and seeking an insight into the mechanisms of the monomer migration under an applied electric field. Methods Some common monomers examined were TEGD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Recent research showed that migration of adhesive monomer in an electric field may be affected by several parameters, including current intensity, chemical structure, and charge of adhesive molecules . The research demonstrated that the migration rate of ionic adhesive monomers correlated directly with the intensity of the applied voltage .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research showed that migration of adhesive monomer in an electric field may be affected by several parameters, including current intensity, chemical structure, and charge of adhesive molecules . The research demonstrated that the migration rate of ionic adhesive monomers correlated directly with the intensity of the applied voltage .…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated in the figure, the EEG pattern recorded during image acquisition was essentially free from artifacts. Typically, gradient-induced artifacts can saturate the EEG signal due to the switching gradients; however, our EEG signals were minimally affected presumably because of the rigidity (minimized vibration in the lead wires), insulation, and circuit-loop area reduction provided by encapsulating the electrode wires with a methylmethacrylate-based orthodontic component resin (Breschi et al, 2012;Khaii et al, 2007;Sword et al, 2008;Van Landuyt et al, 2007;Vasios et al, 2006). PnO stimulation produced a transient artifact in the EEG that typically lasted for 2-3 sec.…”
Section: Physiological Variablesmentioning
confidence: 99%
“…Orthodontic resin (DENTS-PLY Caulk, Milford, DE) was then applied on the left cranium to create one unit (recording electrodes, nylon screw, and stimulating electrode). To minimize the gradientinduced artifact on the EEG, the remaining portion of the platinum recording electrode wires was further insulated using methyl-methacrylate-based orthodontic resin to minimize the circuit loop area through which noise induced by time-varying magnetic fields could be introduced, to provide greater rigidity in order to reduce vibrations in the lead wires (Vasios et al, 2006), and due to its dielectric properties (Breschi et al, 2012;Park et al, 2007;Sword et al, 2008;Tomar et al, 2012;Van Landuyt et al, 2007). The platinum electrodes were then subsequently bent 90°such that the pedestal lay parallel to the dorsal surface of the head.…”
Section: Surgical Preparationmentioning
confidence: 99%
“…Moreover, the tooth model can be further modified to include restorative materials with specified electrical properties [2].…”
Section: Discussionmentioning
confidence: 99%
“…By applying a dc voltage between an application sponge filled with an adhesive and the etched tooth substrate a constant electric flow during the adhesive application is created. An insight into the mechanisms of monomer migration under the application of an electric field can be found in [2], where the electrical properties of the resin monomers are measured and it is shown that the electrophoretic effect is enhanced by high values of electrical conductivity. These findings may be used to quantify the effect of electric currents on impregnation of monomers with a modelling approach.…”
Section: Introductionmentioning
confidence: 99%